Chasing gen Y: Unlocking the reasons for buying branded clothes - Fernandez, P.R.; Lean, M.L. (2009)
This study focuses on the impact of branding on Gen V's choice of clothing as it is hypothesized that they are brand conscious. The research looks' at college students aged between 18 and 24 years old located in the Klang Valley. This study aims to determine if this group of Gen Y are brand conscious in their choice of clothing. In-depth personal interviews were conducted on twenty interviewees for qualitative analysis. The findings suggest that Gen Y are brand conscious; peer influence plays a crucial role in their choice of brands; advertising is an important variable in conferring brand values and establishing an image for the brand; and celebrity endorsements have a huge impact as they promote certain attributes like image, quality and status. The researchers recommend that to retain Gen V's loyalty, brand managers need to build an emotional attachment to make the brand special and bring lasting competitive advantage. Additionally, advertising should be used to not only create awareness but influence brand image and preference. A buzz should be created through celebrity endorsement to reach out to this segment.